Assessing the effects of ENSO-induced climate variability on shallow coastal groundwater reserves of north Patagonia, Argentina - Gaiolini, Mattia (2025)
In this study, a statistical correlation analysis, integrating climatic indices and numerically calculated hydrological datasets, was used to assess the impact of climate patterns and meteorological variability (identified by ONI and SPEI, respectively) on a coastal aquifer in a semi-arid area of Patagonia. To estimate aquifer groundwater levels and flows changes over the 56 years period (1967–2022) under analysis, a 3D numerical flow model was implemented, calibrated against observed piezometric heads and validated using remote sensing data from the GRACE mission. Results highlighted the role of meteoric recharge and evapotranspiration in shaping the water budget, highly affecting the piezometric fluctuation over the simulation. The statistical correlation showed a weak positive association between GW levels and both ONI and SPEI, indicating that climate and meteorological variability are exerting a slight but noticeable influence on groundwater dynamics. Moreover, an increasing seawater inflow from the ocean and tidal channels was observed due to decreasing meteoric recharge and this climate change-driven shift in water exchange dynamics could potentially increase salinization risk in the low-lying areas of this coastal aquifer. The developed methodology could help a proper water resource management in a coastal region where groundwater is the only source of supply for residents, providing useful information for studying groundwater resources in other coastal areas of Patagonia and the world that face similar water problems.